2017
DOI: 10.1186/s13071-017-2536-3
|View full text |Cite
|
Sign up to set email alerts
|

Babesia vesperuginis, a neglected piroplasmid: new host and geographical records, and phylogenetic relations

Abstract: Background Babesia spp. are hemoparasites which infect the red blood cells of a large variety of mammals. In bats, the only known species of the genus is Babesia vesperuginis. However, except a few old reports, the host range and geographical distribution of this bat parasite have been poorly studied. This study aimed to investigate the presence of piroplasms in tissues of bats collected in four different countries from eastern and central Europe: Austria, Czech Republic, Hungary and Romania.MethodsA total of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…megalophylla in South America and in N. noctula in Europe was reported to be 1.19% (2/168) and 1.63% (4/246), respectively [5,7]. However, the prevalence of B. vesperuginis in other bat species might be biased due to the limited sample size [7,8]. In this study, the prevalence of B. vesperuginis in E. serotinus from China was 13.3% (2/15), which might also be biased by the limited sample size.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…megalophylla in South America and in N. noctula in Europe was reported to be 1.19% (2/168) and 1.63% (4/246), respectively [5,7]. However, the prevalence of B. vesperuginis in other bat species might be biased due to the limited sample size [7,8]. In this study, the prevalence of B. vesperuginis in E. serotinus from China was 13.3% (2/15), which might also be biased by the limited sample size.…”
Section: Resultsmentioning
confidence: 99%
“…So far, Babesia spp. detected in bats have been almost exclusively Babesia vesperuginis [5][6][7][8][9], with the exception of a study reporting Babesia canis, the causative agent of canine babesiosis, in the feces of bats from Hungary [10]. In addition, a recent study reported the detection of B. vesperuginis, Babesia crassa and B. canis in ixodid ticks on bats [11], which indicated that bats could harbor a greater diversity of Babesia species and hard ticks could also play a role in Babesia transmission among bats.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nested PCR amplifications targeting the 18S rDNA gene (561 bp) were performed using two sets of primer pairs [33,34]. The amplification profile used was described previously [35]. DNA isolated from the blood of a dog from Romania which was naturally infected with B. canis was used as a positive control.…”
Section: Molecular Assaysmentioning
confidence: 99%